The United Kingdom and the world monetary system - Davies, Brinley (London : Heinemann Educational, 1975)
This book is intended to present clearly, and at a reasonably simple level, the main ideas needed for understanding the role of the United Kingdom in the world monetary system.
Includes index.
Includes bibliographical references: p. 119-121
asm 23/01/2019
Loans
Keywords: Foreign exchange; International finance; Currency question; Great Britain